Making Do With Less: Increasing The Happiness To Consumption Ratio (2009)
The pursuit of happiness is an important goal in consumer behavior, but one that many western cultures do not seem to be achieving through their materialistic-oriented consumption (Sujan, 2008). Based on a review of relevant literature, I proposed seven hypotheses on the relationships between happiness, wealth, entropy of consumption, gratitude, materialism, and individualism. To test these hypotheses, I conducted regression analyses, discussed preliminary results, anticipated potential contributions to the field, and suggested future research possibilities.